Mutual Influence of Reward Anticipation and Emotion on Brain Activity during Memory Retrieval - Yan, Chunping; Liu, Fang; Li, Yunyun; Zhang, Qin; Cui, Lixia (Frontiers in Psychology, 2017)
Previous studies on the joint effect of reward motivation and emotion on memory retrieval have obtained inconsistent results. Furthermore, whether and how any such joint effect might vary over time remains unclear too. Accordingly, using the event-related potential (ERP) measurement of high temporal resolution, our study investigates the cognitive and brain mechanisms of monetary reward and emotion affecting the retrieval processes of episodic memory. Twenty undergraduate and graduate students participated in the research, and our study’s behavioral results indicated that reward (relative to no reward) and negative emotion (relative to positive and neutral emotion) significantly improved recognition performance. The ERP results showed that there were significant interactions between monetary reward and emotion on memory retrieval, and the reward effects of positive, neutral, and negative memory occurred at varied intervals in mean amplitude. The reward effect of positive memory appeared relatively early, at 260–330 ms after the stimulus onset in the frontal-frontocentral area, at 260–500 ms in the centroparietal-parietal area and at 500–700 ms in the frontocentral area. However, the reward effects of neutral and negative memory occurred relatively later, and that of negative memory appeared at 500–700 ms in the frontocentral and centroparietal area and that of neutral memory was at 500–700 ms in the frontocentral and centroparietal-parietal area. Meanwhile, significant FN400 old/new effects were observed in the negative and rewarded positive items, and the old/new effects of negative items appeared earlier at FN400 than positive items. Also, significant late positive component (LPC) old/new effects were found in the positive, negative, and rewarded neutral items. These results suggest that, monetary reward and negative emotion significantly improved recognition performance, and there was a mutual influence between reward and emotion on brain activity during memory retrieval.